1998
DOI: 10.1177/154193129804200102
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pathway Symbology Used to Land from Curved Approaches with Varying Visibility Conditions

Abstract: Global Positioning System technology has the potential to revolutionize both commercial and military aircraft landing procedures. It will enable pilots to fly complex, curved approaches rather than the more simple straight-in approaches necessitated by the Instrument Landing System used at most large airports. To complement this technology, Head-Up Display pathway symbology was developed for use in the aircraft to help pilots stay on course during these complex landings. Thirteen Air Force pilots used this pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…It is unlikely, though, that either a track-up or north-up map display would be used for real-time course guidance during flight. Instead, real-time course guidance would be provided either by a traditional course direction indicator or, in future systems, by some sort of highway-in-the-sky display (Reising, Liggett, Kustra, Snow, Hartsock & Barry, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely, though, that either a track-up or north-up map display would be used for real-time course guidance during flight. Instead, real-time course guidance would be provided either by a traditional course direction indicator or, in future systems, by some sort of highway-in-the-sky display (Reising, Liggett, Kustra, Snow, Hartsock & Barry, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Such complex approaches, with multiple curves and descent rates, may become common in the next decade as augmentation systems to the current GPS signal, both military and civilian, become operational. Later research showed that the benefit of a pathway HUD in landing these approaches did not vary with visibility in three daylight conditions, but did not directly compare the pathway to the MIL-STD HUD (Reising, et al, 1998). While clear differences have been found between pathway and MIL-STD HUD symbology with regard to performance in flying and landing complex approaches, the differential effects of these two symbology sets on situation awareness and workload have yet to be measured.…”
Section: Effects Of Primary Flight Symbology On Workload and Situamentioning
confidence: 99%
“…Previous research (Reising, Liggett, Solz, and Hartsock, 1995) has shown that the pathway HUD used in this study (see Figure 2) improves pilot performance with respect to maintenance of commanded airspeed, altitude, and heading during instrument landings, roughly halving RMS error when compared to a traditional HUD. Further, these benefits have been found regardless of external visibility condition (Reising, Liggett, Kustra, Snow, Hartsock, and Barry, 1998). Unfortunately, other research has demonstrated that, while ego-centered flight path displays improve performance, they also reduce global situation awareness (Olmos, Liang, and Wickens, 1997).…”
Section: Introductionmentioning
confidence: 94%